INNOTEC 2017
DOI: 10.26461/13.12
|View full text |Cite
|
Sign up to set email alerts
|

Producciones de sentido en torno a la exposición a agroquímicos. El caso de la ciudad de Young

Abstract: Producciones de sentido en torno a la exposición a agroquímicos...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…National epidemiology studies in human toxicology have identified a wide range of conditions and diseases associated with environmental exposure to pesticides. Evidence has been found in the working environment, in rural and urban populations associated with agriculture (20)(21)(22) ; and in the general unexposed population (23) .…”
Section: Toxicology and Ecotoxicology Characterization Of Major Used ...mentioning
confidence: 99%
“…National epidemiology studies in human toxicology have identified a wide range of conditions and diseases associated with environmental exposure to pesticides. Evidence has been found in the working environment, in rural and urban populations associated with agriculture (20)(21)(22) ; and in the general unexposed population (23) .…”
Section: Toxicology and Ecotoxicology Characterization Of Major Used ...mentioning
confidence: 99%